Validity and Practicality: Study of E-Poster Development to Improve Environmental Literacy - Yovita; Mery Berlian (Kartika: Jurnal Studi Keislaman, 2026)
The advancement of Industry 4.0 technology has transformed the way humans think and work, making it faster, more efficient, and more effective across various sectors, including education. Universitas Terbuka (UT), as a distance learning university, actively develops learning methods based on online platforms and independent study to support and evaluate the learning system, particularly in laboratory practices. Research shows that the QR Code-based E-Poster developed has high levels of validity, practicality, and effectiveness in improving environmental literacy. The majority of respondents gave positive feedback, including ease of use, good layout, information accessibility, clear text presentation, attractive color composition, good systematic organization, and efficiency in delivering information. In assessing media quality, aspects of readability and conceptual understanding are very important. The conceptual reasoning of respondents in following and understanding the ideas presented in the E-Poster is a significant factor. Ease of reading and understanding the text, as well as the ability to interpret the language used, also support the effectiveness of this media. These findings emphasize the importance of paying attention to design and language aspects in developing E-Posters as effective learning and communication tools in the digital era